FMS Effects of a Motor Program for Children With Autism Spectrum Disorders. Issue 4 (August 2021) - Dong, Liangshan; Shen, Bo; Pang, YanLi; Zhang, Mingting; Xiang, Yuan; Xing, Yu; Wright, Morgan; Li, Dan; Bo, Jin
The current study evaluated the effectiveness of a motor program that specifically targeted fundamental motor skills (FMS) in children with ASD. The experimental group (n=21) participated in a 9-week program with motor instructions for 80 minutes/day, three days/week, while the control group (n=29) did not participate in the program. We measured FMS (using the Test of Gross Motor Development-3) one-week before, one-week after, and two-months after the program. Children in the experimental group had significantly larger FMS improvements than the controls on both locomotor and ball skills immediately following the program, and these participants showed continuous improvement on locomotor, but not ball skills, at 2-months follow-up. In individual analyses, 80% of children in the experimental group versus 29% of children in the control group showed continuous locomotor skills improvement beyond their pre-test levels. These findings highlight the importance of both a long-term motor development intervention and an individualized approach for evaluating improved FMS among children with ASD.